2002
DOI: 10.1037/0893-3200.16.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent satisfaction in family rituals and psychosocial development: A developmental systems theory perspective.

Abstract: Adolescent satisfaction in family rituals and psychosocial development (E. Greenberger & A. B. Sorenson, 1974) were explored in the context of adolescent personality characteristics (International Personality Item Pool, 1999) and family environment characteristics (S. M. Gavazzi, M. J. Reese, & R. M. Sabatelli, 1998; D. H. Olson et al., 1983). Data were collected from 159 female undergraduates with the Adolescent Satisfaction in Family Rituals Scale (D. G. Eaker & L. H. Walters, 1999). Family ritual satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Research has found positive crosssectional associations among meaning of family rituals (Fiese & Kline, 1993), satisfaction with these events (Eaker & Walters, 2002), and perceptions of family cohesion. However, to our knowledge, no study to date has examined the link between family rituals and family cohesion/ belonging over time.…”
Section: Functions Of Family Rituals For Familiesmentioning
confidence: 98%
“…Research has found positive crosssectional associations among meaning of family rituals (Fiese & Kline, 1993), satisfaction with these events (Eaker & Walters, 2002), and perceptions of family cohesion. However, to our knowledge, no study to date has examined the link between family rituals and family cohesion/ belonging over time.…”
Section: Functions Of Family Rituals For Familiesmentioning
confidence: 98%
“…Several studies have established a relationship between investing in family rituals and positive outcomes in school-age children, such as academic success (Fiese et al, 2002). Adolescence studies suggest that youths appreciate family rituals (Eaker & Walters, 2002). Greater family investment in these events is positively correlated with better social skills (Fiese & Wamboldt, 2000), integration, identity, sense of belonging, and self-esteem (Fiese, 1992), lower attendance of psychological/psychiatric support (Compañ , Moreno, Ruiz, & Pascual, 2002); and self-reported well-being in adolescents (Crespo, Carona, Silva, Canavarro, & Dattilio, 2011;Crespo, Kielpikowski, Pryor, & Jose, 2011).…”
Section: Family Interaction Patternsmentioning
confidence: 99%
“…They promote satisfaction and stability (Bruess & Pearson, 2002;Fiese & Tomcho, 2001), ease role transition such as the transition to parenthood (Fiese, Hooker, Kotary, & Schwagler, 1993;Kalmijn, 2010), contribute to a sense of marital and family identity (Braithwaite & Baxter, 1995;Crespo et al, 2008;Doherty, 2001), help transmit family values and beliefs (Friedman & Weissbrod, 2004), and strengthen relationships during times of transition and crisis (Barnett & Youngberg, 2004;Eaker & Walters, 2002). They promote satisfaction and stability (Bruess & Pearson, 2002;Fiese & Tomcho, 2001), ease role transition such as the transition to parenthood (Fiese, Hooker, Kotary, & Schwagler, 1993;Kalmijn, 2010), contribute to a sense of marital and family identity (Braithwaite & Baxter, 1995;Crespo et al, 2008;Doherty, 2001), help transmit family values and beliefs (Friedman & Weissbrod, 2004), and strengthen relationships during times of transition and crisis (Barnett & Youngberg, 2004;Eaker & Walters, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rituals serve a variety of functions in marital and family relationships. They promote satisfaction and stability (Bruess & Pearson, 2002;Fiese & Tomcho, 2001), ease role transition such as the transition to parenthood (Fiese, Hooker, Kotary, & Schwagler, 1993;Kalmijn, 2010), contribute to a sense of marital and family identity (Braithwaite & Baxter, 1995;Crespo et al, 2008;Doherty, 2001), help transmit family values and beliefs (Friedman & Weissbrod, 2004), and strengthen relationships during times of transition and crisis (Barnett & Youngberg, 2004;Eaker & Walters, 2002). In addition to the benefits provided to marital and family relationships, Campbell and Ponzetti (2007) found that rituals enhance commitment for individuals in premarital relationships.…”
Section: Literature Reviewmentioning
confidence: 99%